Exploring the mental health and positive youth development (PYD) of students and the services, opportunities, and supports provided in rural, low socio-economic status (SES) high schools to strengthen student mental health and PYD - Hughes, Jason Erik (Kansas State University, 2021)
This collective case study sought to explore the status of the mental health and Positive Youth Development (PYD) of students attending rural, low socio-economic status (SES) high schools and to identify the school-based services, opportunities, and supports high schools are providing to strengthen student mental health and PYD. The research was guided by the following questions: 1) what factors do students and school staff in rural, low SES high schools identify as contributors to mental health problems in youth and what specific mental health issues do they believe students struggle with the most, 2) how do students and school staff describe the level of confidence, competence, connection, character, compassion, and contribution of students attending rural, low SES high schools and what specific school actions do they believe build and develop these characteristics in students, 3) what specific services, opportunities, and supports do rural, low SES high schools provide to strengthen mental health and the confidence, competence, connection, character, compassion, and contribution of students? This multi-case design began with contacting seven rural, low SES high schools in Kansas and seven in West Virginia. A quantitative survey was conducted with sophomores and juniors in each school. The data collected in the survey were used as a factor in determining the four schools for the collective case study and to triangulate data in the study. In addition to the data from the surveys, conversations via Zoom and phone were conducted with school administrators to ascertain which four schools implemented similar interventions to address student mental health and PYD. Two schools in Kansas and two in West Virginia were selected and a visit was conducted at each school. While at each school, open-ended semi-structured focus group interviews were conducted with two student groups and one school staff group. Observations were made while at the school and pertinent documents were collected for the purpose of answering the research questions and triangulating the data from the focus group interviews. A collective case study with four similar schools was used to provide more robust evidence. The findings of the study illuminate the current status of the mental health and PYD of students attending rural, low SES high schools. Students and school staff together identified pressure, home life, technology, bullying, and stigma as contributors to mental health problems in youth and believed that anxiety, stress, depression, lack of health coping, and suicidal comments were the most pressing mental health issues for students in their schools. PYD levels in each school varied between students but was strongly linked to core academic subjects and school-based opportunities. The modeling, intentionality, words, and actions of adults in schools along with providing students with diverse opportunities and voice emerged as the actions within a school that have the greatest impact on student PYD. Food distribution, access to a licensed mental health therapist or counselor, providing a school-based social resource, after-school programming, robust social-emotional learning interventions, and career, college, and workforce services were the major services implemented by the schools to strengthen student mental health and PYD. Providing student leadership opportunities, co-curricular and extracurricular activities, and college, career, and workplace readiness activities were the major opportunities schools provided students to strengthen their mental health and PYD. Academic supports, teachers, counselors, positive behavior interventions and supports, and trauma informed care were the major supports provided in the schools to strengthen student mental health and PYD. Recommendations are made based on practices discovered in the four schools. Implications for practice include strategies to relieve student pressure and to assist them in navigating problems that arise due to home life, technology, and bullying. Additional strategies for reducing mental health stigma in schools are provided along with ideas on how to build and strengthen the confidence, competence, connection, character, compassion, and contribution of students. Recommendations for future research are also presented.
Keywords: Rural schools; Low socio-economic schools; Student mental health; Positive youth development